Earthworms from Bursa Uludağ Mountain, with first record of Octolasion cyaneum (Savigny, 1826) from Turkey - Misirlioğlu İbrahi̇m Mete (Zootaxa, 2018)
Uludağ is the highest mountain (2.543 m) of the Marmara region in Bursa Province, western Turkey. The Uludağ National Park has rich biodiversity in terms of fauna and flora. Habitats of the park range from maquis on the lower slopes, through deciduous woodland and beech and fir forest to alpine meadows at the highest elevations. The first earthworm records from the Uludağ Mountain were done by Zicsi (1973). His work was continued by Omodeo and Rota (1989, 1991). Species records in these works were based on limited sampling. The current study is the first comprehensive study of earthworms in the Uludağ Mountain area.